2016
DOI: 10.7883/yoken.jjid.2015.054
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Prevalence of Macrolide Resistance among Pediatric <i>Mycoplasma pneumoniae</i> Infections in Hokkaido, Japan

Abstract: SUMMARY:Recently, macrolide-resistant (MR) Mycoplasma pneumonia appeared, and prevalence of macrolide resistance among M. pneumoniae infections varies by country. However, reports on regional differences in the prevalence of MR M. pneumonia within a country are scarce. In this study, 617 nasopharyngeal swab samples were collected from 617 pediatric patients, and DNA of M. pneumoniae was identified in 95 samples. In 51 of the 95 M. pneumonia positive samples, we detected the presence of mutation A2063G mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…The peak season of MP infection was winter in our study, and there was seasonal difference for the prevalence of MP infection, it was higher during winter than that in spring (P< .05). These findings were consistent with the reports that the epidemic seasons in north of China is winter but is summer and autumn in the south of China 8,16 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The peak season of MP infection was winter in our study, and there was seasonal difference for the prevalence of MP infection, it was higher during winter than that in spring (P< .05). These findings were consistent with the reports that the epidemic seasons in north of China is winter but is summer and autumn in the south of China 8,16 .…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study found that 46 clinical isolates collected from 2003 to 2006 were MRMP, the rate of macrolide resistance was as high as 92% in Beijing 3 . Macrolide resistance rates were 3.5-13.2% in USA 45 , below 10% in Europe 6 , 50-90% in Japan 78 and more than 90% in China 3,910 .…”
mentioning
confidence: 95%
“…In Japan, the Infectious Disease Control Law mandates that the number of M. pneumoniae pneumonia cases diagnosed at designated sentinel sites be reported weekly, although these data do not include the prevalence trends of macrolide resistance. The rate of macrolide resistance was shown to vary from 50% to 93% across the seven districts of Japan,24 as well as among areas in the same prefecture ranging from 0 to 100% (Hokkaido) 23. In this study, we employed the GENECUBE system and GENECUBE Mycoplasma detection kit for point‐of‐care molecular examinations, which can determine the presence of M. pneumoniae and MRM within only 1 hour.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting the updated data of MRM determination rates among cases of M. pneumoniae infections may help to predict macrolide shown to vary from 50% to 93% across the seven districts of Japan, 24 as well as among areas in the same prefecture ranging from 0 to 100% (Hokkaido). 23 In this study, we employed the GENECUBE system and to season within the same year, which was possibly because of the change in endemic strains. 25 Therefore, determining the exact trend of prevalence of M. pneumoniae with MRM requires continuous monitoring, conducted locally throughout the year, which could be helpful for the antimicrobial stewardship in primary care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation